Jogo de máscara na epistolografia amorosa entre Fernando pessoa, Ofélia Queiroz e Álvaro de Campos - Scaramussa, Taiga Bertolani (2017)
This study aims at identifying and analyzing, in Fernando Pessoa’s Love Letters (1919- 1935) the hypothesis of an invervention of Pessoa’s heteronym Álvaro de Campos along the love correspondence held by Fernando Pessoa and Ophelia Queiroz, by including the whole four phases of the couple’s relationship. For that matter, we hereby focused on the following aspects, i.e.: a) the bibliographical review on epistolography in Fernando Pessoa in order to identify studies that were already realized and certified by the literary critique; b) displaying of the mains concepts and theorizations on epistolography; c) considerations on Pessoa’s heteronymic project and on its consequences; and d) displaying and analysis of a selected corpus of their love correspondence in order to verify how would Álvaro de Campos intervene in the poet’s love relationship as the implications of this interventive gesture. As our theoretical background there were utilized Geneviève Haroche-Bouzinac’s considerations on epistolography, as well as Brigitte Diaz’s reflections on epistolography as a literary genre, and both Richard Zenith and José Paulo Cavalcanti Filho, for a critical background on Fernando Pessoa, his life and works.